Hypertransaminasemia and liver fibrosis associated with haptoglobin retention and anhaptoglobinemia in a paediatric patient. (16th August 2021) - Gunzer, Sophia; Kraus, Andreas; Buchroth, Inka; Grüneberg, Marianne; Westermann, Cordula; Biskup, Saskia; Reunert, Janine; Grünewald, Inga; Marquardt, Thorsten
Abstract: Cryptogenic elevation of transaminases in childhood can in a few instances be linked to rare hereditary causes. In this paper, a 7‐year old girl is reported who was diagnosed with elevated transaminases of unknown origin since infancy. A liver biopsy showed bridging fibrosis, pale eosinophilic intracytoplasmic hepatocellular inclusions and enlarged endoplasmic reticulum cisternae in the hepatocytes. Whole‐exome sequencing revealed a homozygous in‐frame deletion of 3 base pairs in the haptoglobin gene. The patient is anhaptoglobinemic measured by standard laboratory turbidometry, which was confirmed by Western Blotting and thereby shown to affect both protein chains of haptoglobin. A polyclonal antibody revealed haptoglobin retention in hepatocytes suggesting a defect in haptoglobin secretion. A novel, previously unknown haptoglobin storage disease is suspected to be the reason for the elevated liver enzymes and tissue abnormalities in this patient. The pathophysiology appears to be similar to endoplasmic reticulum storage diseases like alpha‐1‐antitrypsin‐deficiency.